2020
DOI: 10.1111/nmo.13957
|View full text |Cite
|
Sign up to set email alerts
|

Irritable Bowel Syndrome: Straightening the road from the Rome criteria

Abstract: The concept of positive diagnosis of irritable bowel syndrome (IBS) based on symptoms kicked off with studies from the University of Bristol; Manning et al identified 4 symptoms that were clearly more common in patients with IBS: abdominal distension as evidenced by tight clothing or visible appearance; pain relief with bowel action; more frequent stools with the onset of pain; and looser stools with the onset of pain. 1 Justification for the development of symptom-based criteria for irritable bowel syndrome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
1
17
0
7
Order By: Relevance
“…3,7 In general, the prevalence of IBS tends to decrease when the stricter Rome IV criteria for abdominal pain are applied, since many patients with an IBS diagnosis according to the previous criteria are now classified as having other functional lower gastrointestinal disorders. 14 Similar trends were reported in a recent systematic review on the global prevalence of IBS according to Rome IV criteria. 5 A recent local study showed that the prevalence of IBS according to Rome IV criteria was significantly higher compared with that reported by previous local studies that used the older Rome criteria.…”
Section: Prevalence and Clinical Characteristics Of Ibs In Vietnamesesupporting
confidence: 82%
“…3,7 In general, the prevalence of IBS tends to decrease when the stricter Rome IV criteria for abdominal pain are applied, since many patients with an IBS diagnosis according to the previous criteria are now classified as having other functional lower gastrointestinal disorders. 14 Similar trends were reported in a recent systematic review on the global prevalence of IBS according to Rome IV criteria. 5 A recent local study showed that the prevalence of IBS according to Rome IV criteria was significantly higher compared with that reported by previous local studies that used the older Rome criteria.…”
Section: Prevalence and Clinical Characteristics Of Ibs In Vietnamesesupporting
confidence: 82%
“…In addition, the Rome IV criteria include ‘abdominal pain’ and exclude ‘abdominal discomfort’, and also include more stringent frequency criteria. The use of the Rome IV criteria has greatly reduced the prevalence of reported IBS, so this system may be less suitable for an epidemiological survey such as this one ( 8 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Rome Foundation consensus process has also been criticized for its symptom‐based and symptom‐clustering approach and for the anatomical basis of its subdivision. In this issue of Neurogastroenterology and Motility , Dr. Michael Camilleri contributed a paper arguing in favor of abandoning diagnoses based on symptom clusters for bowel disorders, to focus on the identification of underlying pathophysiological mechanisms to guide diagnosis and treatment, with a focus on bowel disorders 6 . Even though most active clinical researchers within this field, including the authors of this article, aim toward finding support for a more pathophysiology‐ or biomarker‐based approach in the clinical management and diagnostic approach to these patients, there is insufficiently robust scientific evidence for widely introducing this approach in the general clinical setting.…”
Section: Other Intestinal Symptoms Related To Ibs Other Digestive Symmentioning
confidence: 99%